Using a MDMA- and LSD-Group Therapy Model in Clinical Practice in Switzerland and Highlighting the Treatment of Trauma-Related Disorders - Oehen, Peter; Gasser, Peter (Frontiers in Psychiatry, 2022)
The Swiss Federal Act on Narcotics allows for the restricted medical use of scheduled psychotropic drugs in cases of resistance to standard treatment, and preliminary evidence of efficacy of the scheduled drug for the particular condition. Since 2014, the authors have obtained 50 licenses on a case-by-case basis and developed a psychedelic-assisted group therapy model utilizing MDMA and LSD. The majority of the patients taking part in the psychedelic group therapy suffered from chronic complex post-traumatic stress disorder (c-PTSD), dissociative, and other post-traumatic disorders. Treatment modalities, typical developments and problems encountered during and after the psychedelic experiences are described. Recurrent depression poses a frequent problem, and requires special attention. Symptoms of c-PTSD predominantly addressed by the psychedelic experiences are the regulation of emotions and impulses, negative self-perception, alterations in relationships to others, as well as meaning, recall, and processing of traumatic memories. C-PTSD needs a larger number of psychedelic experiences in contrast to PTSD resulting from single trauma. In this model MDMA was most often used in the first phase to enhance motivation to change, strengthen the therapeutic alliance, allowing it to become more resilient, stress-relieved and less ambivalent. When emotional self-regulation, negative self-perception and structural dissociation had also begun to improve and trauma exposure was better tolerated, LSD was introduced to intensify and deepen the therapeutic process. The majority of participants improved by clinical judgement, and no serious adverse events occurred. A short case vignette describes a typical process. The experiences with this model can serve to further develop the method of psychedelic-assisted psychotherapy (PAP) and to give directions for future research.